Enhanced Degradation of Lactide-co-Glycolide Polymer with Basic Nucleophilic Drugs. (26th January 2015) - D'Souza, Susan; Faraj, Jabar A.; Dorati, Rossella; DeLuca, Patrick P.
Abstract : The purpose of this study was to examine the degradative effect of weakly basic nucleophilic drugs on a lactide-co-glycolide (PLGA) polymer in a microsphere formulation. Biodegradable PLGA microspheres of two second-generation atypical antipsychotics, Risperidone and Olanzapine, were manufactured using a solvent extraction/evaporation technique. The effect of drug content, buffer pH and temperature on polymer molecular weight and degradation, were examined via a series of experiments and compared against a control (Placebo PLGA microspheres). In comparison to Placebo microspheres, significant polymer molecular weight reduction was observed upon encapsulation of varying levels of either Risperidone or Olanzapine. There was excellent correlation between the extent of molecular weight reduction during manufacture and the amount of encapsulated drug in the microspheres. Subsequent studies on polymer degradation showed: the following (a) the Placebo and Olanzapine microspheres followed pseudo first order kinetics, (b) Risperidone microspheres exhibited biphasic degradation profiles, and (c) polymer degradation was dependent on temperature, not pH. The findings of these studies show that encapsulation of weakly basic nucleophile type drugs into PLGA can accelerate the biodegradation of the PLGA and have major implications on the design of polymeric microsphere drug delivery systems.